2016
DOI: 10.1590/s0100-83582016340200012
|View full text |Cite
|
Sign up to set email alerts
|

Phytosociological Survey and Weed Interference in Eggplants Cultivation1

Abstract: -Eggplants are vegetables of great importance in the South and Southeast regions of Brazil, which are subject to interference from weeds. In order to collaborate with weed management in this vegetable, this study was carried out to determine the periods of weed interference in growing eggplants. The study was conducted in the Brazilian municipality of Jaboticabal, SP, at the Faculty of Agricultural and Veterinary Sciences, UNESP [Universidade Estadual Paulista "Júlio de Mesquita Filho" (São Paulo State Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…E. indica, stand out for using more efficiently high temperatures and luminosity (Christin et al, 2014;Venâncio et al, 2014), conferring higher photosynthetic rates due to the wide spacing between the planting lines and the long period of time for shading the interrows by eggplant crop. However, large and longercycle plants, such as N. physaloides, tend to dominate the field in more advanced stages of the cycle, as observed by Marques et al (2016Marques et al ( , 2017 and other authors.…”
Section: Macronutrientsmentioning
confidence: 51%
See 4 more Smart Citations
“…E. indica, stand out for using more efficiently high temperatures and luminosity (Christin et al, 2014;Venâncio et al, 2014), conferring higher photosynthetic rates due to the wide spacing between the planting lines and the long period of time for shading the interrows by eggplant crop. However, large and longercycle plants, such as N. physaloides, tend to dominate the field in more advanced stages of the cycle, as observed by Marques et al (2016Marques et al ( , 2017 and other authors.…”
Section: Macronutrientsmentioning
confidence: 51%
“…These authors observed that E. indica was more important at the beginning of the crop cycle due mainly to the plant density, while N. physaloides, a species with slower initial growth and longer cycle, was more important at the end of the cycle due to the accumulation of biomass. Both species E. indica and N. physaloides are common in fields of vegetables (Marques et al, 2016), as observed in other crops, such as okra, tomato, beet etc. Therefore, at the beginning of the cycle, the C4 weeds, e.g.…”
Section: Macronutrientsmentioning
confidence: 87%
See 3 more Smart Citations